Harnessing aggregation-induced emission property of indolizine derivative as a fluorogenic bioprobe for endoplasmic reticulum - Arun, V.; Choi, Sang Kee; Han, Ji Hye; Choi, Hongseo; Kim, Hyung Mo; Kim, Wook; Choi, Junwon; Kim, Jonghoon; Kim, Eunha (Dyes and Pigments, 2022)
For fluorogenic bioimaging of the endoplasmic reticulum, a new aggregation-induced emission luminogen (AIEgen) core skeleton was conjugated with glibenclamide. Click chemistry was successfully employed for the efficient conjugation between azide-modified glibenclamide and alkyne-containing indolizine core skeleton to generate Aru68. When the volume fraction of water is increases in the solution of Aru68 in water and DMF induced aggregates formation and simultaneous increase of fluorescence intensity up to 100-fold was observed. Solvatochromism and restriction of molecular motion study by perturbation of solvent polarity index and volume fraction of glycerin in glycerin/methanol mixture provided a mechanistic insight into the turn-on phenomenon of Aru68 as AIEgen. The final bio-imaging demonstration of Aru68 in live cell conditions revealed great potential not only of the probe for wash-free bioimaging of the endoplasmic reticulum but also of the indolizine core skeleton for efficient fluorogenic bioprobe development based on aggregation-induced emission processes.
Keywords: Aggregation-induced emissions; Bio-imaging; Bioprobe; Emission properties; Endoplasmic reticulum; Fluorescence imaging; Fluorogenics; Glibenclamide; Indolizine derivative; Indolizines; Aggregation-induced emission; Endoplasmic reticulum; Fluorescence imaging; Glibenclamide; Indolizine